Can ESG Save Zombie Companies During the Covid-19 Pandemic? - Revaldo Farrel Witanto; Tan Ming Kuang (Universitas Pendidikan Indonesia, 2024)
This study examines the relationship between Environmental, Social, and Governance (ESG) and the zombie firm phenomenon. The study employs secondary data from the data provider Revinitif Eikon, encompassing companies listed on the Indonesia Stock Exchange (IDX) between 2018 and 2021, excluding the financial sector, and employing purposive sampling techniques for data collection. The collected data was then analyzed through logistic regression using SPSS software version 26. The findings indicate that ESG harms zombie companies, which suggests that ESG can prevent companies from becoming zombies. Companies with higher levels of ESG implementation are less likely to become zombies. This suggests that companies with strong ESG practices are more resilient to economic instability, especially during the COVID-19 pandemic. This study contributes to the literature on zombie companies and ESG and supports stakeholder theory and the triple bottom line concept. This study has practical implications for company management, providing insights on how to implement ESG principles in operational practices to ensure long-term sustainability. This study introduces novelty by integrating the context of the COVID-19 pandemic to investigate the correlation between ESG and zombie firms, while also adopting the more rigorous theoretical framework proposed by Hoshi et al., (2012) in assessing zombie companies, in contrast to Ren et al., (2022).